Everyday heat transfer problems : sensitivities to governing variables - Atesmen, M. Kemal (American Society of Mechanical Engineers, 2009)
This book uses everyday practical examples to illustrate sensitivities of heat transfer problems to governing variables in a concise and readable format. Examples include cooling of a chip, sizing a solar collector for a pool, cooking a turkey, solar tanning, ice formation on a lake, and more. This book is intended for engineering researchers and advanced students concerned with Heat Transfer problems, as well as industry professionals in a variety of settings. Professionals in electronics packaging, power generation, equipment design and manufacturing, components testing and analysis, and others, will benefit from a better understanding of applied heat transfer issues in their work.
Title from PDF title page (ASME eBooks Web site, viewed 12/04/2010).
Keywords: Heat -- Transmission -- Problems, exercises, etc.; Materials -- Thermal properties -- Problems, exercises, etc.; Thermal conductivity -- Problems, exercises, etc.; Engineering mathematics -- Problems, exercises, etc.; elektronické knihy; electronic books